Changes of serum lipocalin-2 and retinol binding protein-4 levels in patients with psoriasis and Behcet's disease - Gul, Feride Coban; Cicek, Demet; Kaman, Dilara; Demir, Betul; Nazik, Hulya (John Libbey Eurotext Ltd, 2015)
[Abstract Not Available]
Keywords: Insulin-Resistance; Obesity